Kinetika Reaksi Pembuatan Sabun dan Pemurnian Gliserol dari Limbah Alkali Sabun: Review - Panjaitan, Jabosar Ronggur Hamonangan (Universitas Trunojoyo Madura, 2021)
Soap is a product that commonly used as a cleanser and can be made through a saponification reaction between fat and base with glycerol as byproduct. The reaction kinetics of soap production is the study of how fast the soap production and it is an important part in reactor modeling and the optimization of operating conditions. On the other hand, glycerol is a byproduct of soap production which can be applied into various derivative products so that the glycerol purification process from soap production process is important to do. This review discusses the reaction kinetics of soap production and glycerol purification from alkaline soap waste. In general, the kinetics curve of the soap-making reaction consists of three stages, namely the induction period, the constant velocity period and the decreasing velocity period where the base concentration in the soaping reaction was related to the reaction rate. The lower base concentration used, the soap production reaction will slower. The soap production reaction had low activation energy and identified as second order reaction. In the process of purifying glycerol from alkaline soap waste, three main stages were generally used, namely neutralization, alcohol separation and glycerol purification.